Preoperative discussion with patients about delirium risk: are we doing enough?. Issue 1 (December 2016) - Tomlinson, Judith; Partridge, Judith
Abstract Postoperative delirium is a common complication in the older surgical population, occurring in 10–50 % of cases. It is thought to be more common if an individual is identified as frail. Postoperative delirium is associated with poor outcome including higher mortality rates, prolonged length of hospital stay, increased care needs on discharge and longer term post-traumatic stress disorder. Guidelines from the American Geriatric Society and the National Institute for Health and Care Excellence highlight the importance of risk assessment at the time of the preoperative visit. This enables the perioperative team to plan a care pathway that minimises the risk of delirium occurring postoperatively. Risk assessment also informs a discussion with patient and family regarding their risk, as part of a process of informed patient consent. This is an essential step in conforming to current legal and General Medical Council guidance on the process of consent.